PERBEDAAN CARA EKSTRAKSI JAHE DAN PENAMBAHAN GULA KELAPA TERHADAP MUTU SIRUP JAHE - Sagala, Murdiono Abraham; Efendi, Raswen; ', Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This purpose of research is to find out the best grade of ginger syrup from the different methods of extraction and adding palm sugar. This experiment research used Rancangan Acak Lengkap (RAL) with six treatments as follows: P1 (ginger extract (using chopping extraction) and adding 65% palm sugar) P2 (ginger extract (using chopping extraction) and adding 70% palm sugar) P3 (ginger extract (using chopping extraction) and adding 75% palm sugar) P4 (ginger extract (using crushing extraction) and adding 65% palm sugar) P5 (ginger extract (using crushing extraction) and adding 70% palm sugar) P6 (ginger extract (using crushing extraction) and adding 75% palm sugar). The result of this research showed that the methods of ginger extraction and differentces palm sugar concentration influenced the sucrose level,descriptive tested (color, ginger aroma, and the sweetness), hedonic tested (aroma, taste, and as a whole) and there are no pH differences. Descriptive tested (ginger aroma and spiciness) and hedonic tested (color). P6 (ginger extract (using crushing extraction) and adding 75% palmsugar) produce a better syrup. This ginger syrup has 4,07 pH, 68,28 of sucrose level and descriptive tested color and hedonic tested liked by the panelist, the ginger aroma and the sweetness more dominant and contain IC50 up to 38,731μL.   Key words: syrup, palm sugar, ginger and extraction.